Personal space and other essays - Santos, Chit Roces- (Mandaluyong City Anvil Publishing, Inc., 2013)
Personal essays on various aspects of the author's life
Tac-1259g donated by Daniel Matutina on Sept. 19, 2014.
Keywords: Philippine essays (English)